Biocontrol Using Bacillus amyloliquefaciens PP19 Against Litchi Downy Blight Caused by Peronophythora litchii - Zheng, Li; Huang, Shilian; Hsiang, Tom; Yu, Guohui; Guo, Dongliang; Jiang, Zide; Li, Jianguang (Frontiers in Microbiology, 2021)
Bacillus amyloliquefaciens has been widely used in the agriculture, food and medicine industries. Isolate PP19 was obtained from the litchi fruit carposphere and showed biocontrol efficacy against litchi downy blight (LDB) whether applied preharvest or postharvest. To further understand the underlying regulatory mechanisms, the genome of PP19 was sequenced and analyzed. The genome comprised a 3847565 bp circular chromosome containing 3990 protein-coding genes and 121 RNA genes. It has the smallest genome among 36 sequenced strains of B. amyloliquefaciens except for RD7-7. In whole genome phylogenetic analysis, PP19 was clustered into a group with known industrial applications, indicating that it may also produce high-yield metabolites that have yet to be identified. A large chromosome structural variation and large numbers of single nucleotide polymorphisms (SNPs) between PP19 (industrial strain) and UMAF6639 (plant-associated strain) were detected through comparative analysis, which may shed light on their functional differences. Preharvest treatment with PP19 enhanced resistance to LDB, by decreasing the plant H2O2 content and increasing the SOD activity. This is the first report of an industrial strain of Bacillus amyloliquefaciens showing a plant-associated function and with major potential for the biocontrol of LDB.